Deep and intermediate complex morphophysiological dormancy in seeds of Ferula gummosa (Apiaceae). Issue 3 (20th May 2019) - Zardari, Sanaz; Ghaderi‐Far, Farshid; Sadeghipour, Hamid R.; Zeinali, Ebrahim; Soltani, Elias; Baskin, Carol C.
Abstract: We tested the hypothesis that seeds of the monocarpic perennial Ferula gummosa from the Mediterranean area and central Asia have deep complex morphophysiological dormancy. We determined the water permeability of seeds, embryo morphology, temperature requirements for embryo growth and seed germination and responses of seeds to warm and cold stratification and to different concentrations of GA3 . The embryo has differentiated organs, but it is small (underdeveloped) and must grow inside the seed, reaching a critical embryo length, seed length ratio of 0.65–0.7, before the seed can germinate. Seeds required 9 weeks of cold stratification at <10°C for embryo growth, dormancy break and germination to occur. Thus, seeds have morphophysiological dormancy (MPD). Furthermore, GA3 improved the germination percentage and rate at 5°C and promoted 20 and 5% germination of seeds incubated at 15 and 20°C, respectively. Thus, about 20% of the seeds had intermediate complex MPD. For the other seeds in the seed lot, cold stratification (5°C) was the only requirement for dormancy break and germination and GA3 could not substitute for cold stratification. Thus, about 80% of the seeds had deep complex MPD. Abstract : The embryo has differentiated organs and must grow inside the seed. Seeds of Ferula gummosa have morphophysiological dormancy (MPD).